Pengaruh Pendekatan Concrete Pictorial Abstract terhadap Pemahaman Konseptual Peserta Didik - Whendika Retno Setyowati; Uswatun Hasanah (The Elementary Journal, 2026)
The low conceptual understanding of mathematics in elementary schools is often caused by learning practices that ignore the cognitive phase of students, which is the background of this research. This study aims to test whether or not there is and how much influence the concrete pictorial abstract approach has on students' conceptual understanding of plane geometry material. A quantitative approach with a quasi-experimental research type was used in this study. The sampling technique used was saturated sampling which is included in nonprobability sampling. The data collection technique was carried out through written tests in the form of pretests and posttests. The data analysis technique used was the normality and homogeneity test as prerequisite tests. The Independent Sample T-test and Cohen's d test were used for hypothesis testing. The results of the study showed that (1) There is an influence of the concrete pictorial abstract approach on students' conceptual understanding of plane geometry material, as shown in the results of the Independent Sample T-test with a Sig. value of 0.001 (≤ 0.05), so that Ha1 is accepted and Ho1 is rejected. (2) There is a large influence of the concrete pictorial abstract approach on students' conceptual understanding of the material on flat shapes, as shown by the results of the Cohen's d test with a d value of 1.31 (≥ 0.8), so that Ha2 is accepted and Ho2 is rejected. The results of the study confirm that the implementation of concrete pictorial abstracts increases students' conceptual understanding statistically and has practical significance.